ISOLATION, CHARACTERIZATION AND SCREENING OF ANTAGONISTS OF PSEUDOMONAS TOLAASII FOR BIOLOGICAL CONTROL - R. S. SAMSON2; J. GUILLAUMES2, P. K. KHANNA1, J.M. OLIVIER2 (Indian Phytopathology, 2002)
A study of the tuffeau based French casing mixtures indicated that fluorescent pseudomonads sometimes represented more than 50 per cent of the total bacterial population belonging to P. fluorescence and P. putida. Certain isolates having a few characters of both these species were classified as intermediate group, thereby establishing a continuum from P. fluorescence to P. putida. A further splitting into subgroups A and B of this group was possible. Many isolates caused complete suppression in the appearance of blotch symptoms on whole mushroom caps and blocks when tried in combination with pathogenic P. tolaasii. One of these biological antagonists, an isolate of P. fluorescens biover 1 proved quite effective in controlling the blotch incidence on Aqaricus bisporus beds